Implementasi Akad Musyarakah dalam Ekosistem Metavers: Analisis Peluang dan Tantangan Pembiayaan Syariah di Era Digital - Raviqa Noer Laily; Fauzan Fauzan (AL-UJRAH, 2025)
This study analyzes the implementation of musyarakah contracts in the metaverse ecosystem as sharia financing innovations in the digital era. Using descriptive qualitative research methods and Islamic legal analysis, this study explores the opportunities and challenges of applying the principles of sharia partnership in a virtual space. The results of the study show that the metaverse opens up new opportunities for sharia financing through virtual property investments, digital businesses, and blockchain-based economies. However, there are significant challenges related to sharia compliance, regulations, and technical aspects of implementation. This research contributes to the development of digital Islamic finance literature and provides practical recommendations for the Islamic banking industry.